Hold-up in multiple banking: Evidence from SME lending - Antje Brunner; Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
This paper analyzes loan pricing when there is multiple banking and borrower distress. Using a unique data set on SME lending collected from major German banks, we can instrument for effective coordination between lenders, carrying out a panel estimation. The analysis allows to distinguish between rents that accrue due to single bank lending, rents that accrue due to relationship lending, and rents that accrue due to the elimination of competition among multiple lenders. We find the relationship lending to have no discernible impact on loan spreads, while both single lending and coordinated multiple lending significantly increase the spread. Thus, contrary to predictions in the literature, multiple lending does not insure the borrower against hold-up.
urn:nbn:de:hebis:30-78605
Keywords: D74; G21; G33; G34; 330; Banking Competition; Coordination; Distress; Credit Spread; Hold-up; Kreditgeschäft; Zins; Risikoprämie; Firmenkundengeschäft; Klein- und Mittelunternehmen; Bank; Wettbewerb; Lieferanten-Kunden-Beziehung; Sunk Costs; Schätzung; Deutschland